Transformative Strategies to Enhance Teacher Innovativeness: Addressing Challenges Through Strengthening Organizational Culture, Transformational Leadership, Self-Efficacy, and Achievement Motivation - Adhinugraha, R. Bukit Adhinugraha; Soewarto Hardhienata; Widodo Sunaryo; Abdul Wahid Zaini; M. Fathor Rozi (Managere: Indonesian Journal of Educational Management, 2024)
Research generally aims to produce strategies and ways to increase teacher innovation through efforts to identify the magnitude of the direct and indirect influence of Organizational Culture, Transformational Leadership, Self-Efficacy and Achievement Motivation. The research used survey methods and path analysis techniques which were then carried out by SITOREM analysis.  The population in the study was 269 people with a sample taken randomly of 161 teachers using the Taro Yamane formula. The research results prove that there is an influence of Organizational Culture (by1 = 0.176), Transformational Leadership (by2 = 0.053), Self-Efficacy (by3 = 0.188), and Achievement Motivation (by4 = 0.156) on Teacher Innovativeness.  Furthermore, the results of the SITOREM analysis found that the Organizational Culture variable needs to be improved on the indicators: Human Relations in the Organization, Signals, Human Relations with the Environment. The Transformational Leadership variable needs to be improved on the indicators: Intellectual Simulation, Ideal Influence, Inspirational Motivation. The Self-Efficacy variable needs to be improved on the indicators: Past Performance, Experience or Observation of Other People. The Achievement Motivation variable needs to be improved on the indicators: Enjoyment of Facing Challenges and Competition, Need to Work Intensively. It can be concluded that Teacher Innovativeness can be increased through strengthening Organizational Culture, Transformational Leadership, Self-Efficacy, and Achievement Motivation.